Progress in Optoelectronic Oscillators - Raut, Nabin K.; Miller, Jeffery; Sharping, Jay (Journal of Institute of Science and Technology, 2019)
An optoelectronic oscillator (OEO) generates a spectrally pure and ultra-stable radio frequency signal from a continuous wave laser source (Yao et al. 2004). In a conventional electrical oscillator, the energy storage capacity is limited, which compromises stability of the signal. To address this issue, Yao and Maleki invented the optoelectronic oscillator in 1996. This novel oscillator uses low-loss optical fiber to extend the length of the oscillator and thereby increases the amount of energy that can be stored (Madjar & Tibor 2006). Due to this additional energy storing component in the system, the purity and stability of the signal increase significantly. Following their invention, many modifications have been made over the years to improve the frequency stability of OEOs (lower phase noise and timing jitter). This review article discusses some of those key developments and then introduces some ongoing work devoted to understanding the impact of using electrical filters with Q >109.